Enterovirus 71 structural viral protein 1 promotes the expression of PMP22 through m6A modification in mouse Schwann cells - Qiuyan Peng; Guangming Liu; Danping Zhu; Suyun Li; Sida Yang; Peiqing Li; Yingxian Yin; Dandan Hu (Virus Research)
Purpose: Enterovirus 71 (EV71) is one of the enteroviruses that causes hand-foot-and-mouth disease (HFMD). This study aims to investigate the role of EV71 structural viral protein 1 (VP1) in mouse Schwann cells. Methods: An EV71 VP1-expressing vector was generated and transfected into mouse Schwann cells (MSCs). Small interfering RNAs against methyltransferase-like protein 14 (METTL14) and YTH N6-Methyladenosine RNA Binding Protein 1 (YTHDF1) were used to knock down the expressions of METTL14 and YTHDF1 in MSCs to investigate their roles in peripheral myelin protein 22 (PMP22) expression. Real-time PCR and Western blot analysis were performed to determine the expressions of PMP22 and m6A modification-associated proteins. Results: EV71-VP1 over-expression significantly increased the expressions of transmethylase METTL3/14 and m6A methylation recognition protein YTHDC1 and YTHDF1/2/3 in MSCs. On the contrary, the level of demethylase FTO, but not ALKBH5, was obviously decreased in VP1-over-expressed MSCs. Furthermore, 3-DZA inhibited expressions of METTL3/14 and YTHDF1/2 in VP1-over-expressed MSCs, indicating METTL3/14 and YTHDF1/2 were the key m6A-modification-related genes regulated by VP1. In addition, deficiency of METTL14 or YTHDF1 contracted the up-regulation of PMP22 induced by VP1 overexpression in MSCs. Conclusions: VP1 up-regulated PMP22 via m6A modification in MSCs, which were mainly affected by METTL14 and YTHDF1.